Activation of the innate immune response by endogenous retroviruses. - Hurst, T; Magiorkinis, G (Microbiology Society, 2015)
The human genome comprises 8 % endogenous retroviruses (ERVs), the majority of which are defective due to deleterious mutations. Nonetheless, transcripts of ERVs are found in most tissues, and these transcripts could either be reverse transcribed to generate ssDNA or expressed to generate proteins. Thus, the expression of ERVs could produce nucleic acids or proteins with viral signatures, much like the pathogen-associated molecular patterns of exogenous viruses, which would enable them to be detected by the innate immune system. The activation of some pattern recognition receptors (PRRs) in response to ERVs has been described in mice and in the context of human autoimmune diseases. Here, we review the evidence for detection of ERVs by PRRs and the resultant activation of innate immune signalling. This is an emerging area of research within the field of innate antiviral immunity, showing how ERVs could initiate immune signalling pathways and might have implications for numerous inflammatory diseases.